1996
DOI: 10.1538/expanim.45.347
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Male or Female Primordial Germ Cells of Quail into Chick Embryonic Gonads.

Abstract: Blood from an individual quail embryo at stages 13-16, when primordial germ cells (PGCs) were in circulation, was taken from its marginal vein and transfused into the marginal vein of a chick embryo at stages 13-16. Both donor and recipient embryos were cultured in vitro until day 8 of development and their sex was determined by morphological and histological observations of the gonads. Sections of recipient gonads were stained immunohistochemically with QCR1 monoclonal antibody positive for quail PGCs but neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 20 publications
0
34
0
3
Order By: Relevance
“…Yasuda et al (1992) reported that 63.6% of 100 chick PGCs transferred into quail embryos were present in the gonadal anlage. Furthermore, Ono et al (1996Ono et al ( , 1998aOno et al ( , 1998b reported the migration of chick and quail PGCs following the transfer of embryonic blood containing circulating PGCs. From these studies of the migratory ability of PGCs, it has been postulated that PGCs are chemically attracted by unknown substances released from the developing gonads (Kuwana and Roguska, Journal of Poultry Science, 50 (1) 4 Fig.…”
Section: Conservation Of Avian Genetic Resources Through Germline Chimentioning
confidence: 99%
“…Yasuda et al (1992) reported that 63.6% of 100 chick PGCs transferred into quail embryos were present in the gonadal anlage. Furthermore, Ono et al (1996Ono et al ( , 1998aOno et al ( , 1998b reported the migration of chick and quail PGCs following the transfer of embryonic blood containing circulating PGCs. From these studies of the migratory ability of PGCs, it has been postulated that PGCs are chemically attracted by unknown substances released from the developing gonads (Kuwana and Roguska, Journal of Poultry Science, 50 (1) 4 Fig.…”
Section: Conservation Of Avian Genetic Resources Through Germline Chimentioning
confidence: 99%
“…Chimeric birds have also been produced by PGCs transfer from quail to chicken embryos (Ono et al 1996;. PGCs are not thought to be involved in determining sex, and the cells usually differentiate to the germ cells of the sex which has already been determined according to the somatic sex.…”
Section: Discussionmentioning
confidence: 99%
“…PGCs circulate in the vascular system of the developing embryo and finally migrate into the germinal ridge (Fujimoto et al 1976;Kuwana 1993), where the cells differentiate into spermatogonia or oogonia. PGC transfer between embryonic blood vessels is a common technique for establishment of germ line chimeric chickens (Naito et al 1994;Ono et al 1996;Yamaguchi et al 2000;Furuta et al 2001), and it has been reported that exogenous genes may be introduced into PGCs to produce transgenic chicken (Naito et al 1998;Inada et al 1997;Eguma et al 1999;. For confirmation that transfer of PGCs is technically possible, quail PGCs have been H. Furuta (&) Á T. Sawada Á K. Nishikawa Á I. Yamamoto Á T. Yoshida Á M. Tanaka Department of Animal Science, Nippon Veterinary and Life Science University, Kyounan-cho 1-7-1, Musashino, Tokyo 180-8602, Japan e-mail: fhiroki@nvlu.ac.jp observed in chicken gonads using immunohistochemistry (Ono et al 1998), and the capability of producing chimeric chickens has been investigated by progeny testing (Naito et al 1994;Furuta et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the generation of chimeric chickens using PGCs as donors and developing embryos as recipients (Vick et al, 1993a;Naito et al, 1994Naito et al, , 1998Ono et al, 1996Ono et al, , 1998aFuruta et al, 1999Furuta et al, , 2001Furuta et al, , 2007Furuta et al, , 2008Furuta and Fujihara, 1999;Yamaguchi et al, 2000). This study primarily focuses on germline chimeric chickens, the conservation of genetic resources, and the transfer of PGCs, including the introduction of exogenous genes.…”
Section: Introductionmentioning
confidence: 99%